Usborne Phonics Readers : Underpants for Ants - Russell Punter (London, United Kingdom Usborne Publishing Ltd, 2018)
The ants are feeling a bit chilly - can Mouse help with her knitting skills? Press the buttons on the pages to hear this entertaining story read aloud, helping beginner readers learn to read themselves. With simple rhyming text, colourful illustrations and parents' notes on phonics at the back of the book.
Keywords: PY - Language